Balochistan main Tazkara Ṣaḥābah o Tabi‘īn - Dr. Abdul Fareed Brohi; Dr. Shahzad Channa; Khoso, Dr Aijaz Ali (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Balochistan is the largest province of Pakistan, spreads over a 347,190 Sq.Kms forming 43% of the total area of Pakistan. Geographically it is one of the important provinces of Pakistan.Islam reached this area in the 1st century of Hijrah during the last era (23rd Hijri/644 CE) of Hazrat Umar (R.A), when the Islamic forces were offering jihad in Kirman, the region of Iran, under the command of Ameer Basra, Hazrat Abu Musa Ashari(R.A) and Ameer Bahrain Hazrat Usman bin Abi-Alas(R.A). Hazrat Usman bin Abi-Alas sent a force to Makran (Balochistan) under the command of his brother Hazrat Hakam bin Abi-Alas, which got great achievements. After the conquest of Makran, a series of victories started which continued in the period of Hazrat Usman, Hazrat Ali and in the period of Umayyad caliphate. A large number of the Companions of the Prophet (Sahaba) and Tabaeen came here. Some of them were martyred and buried here. There are many of their graves in different parts of Balochistan. Different tribes came under the umbrella of Islam which has a great effect on their lives, culture and civilization. This paper is an attempt to explore the efforts of the early Muslims who came here and spread the message of Islam in the areas which are now in the present day Pakistan.